Acute Effects of Esports on the Cardiovascular System and Energy Expenditure in Amateur Esports Players - Zimmer, Rebecca T.; Haupt, Sandra; Heidenreich, Heiko; Schmidt, Walter F. J. (Frontiers in Sports and Active Living, 2022)
Introduction: Esports is practiced by millions of people worldwide every day. On a professional level, esports has been proven to have a high stress potential and is sometimes considered equivalent to traditional sporting activities. While traditional sports have health-promoting effects through muscle activity and increased energy expenditure, amateur esports could represent a purely sedentary activity, which would carry potentially harmful effects when practiced regularly. Therefore, this study aims to investigate the acute effects of esports on the cardiovascular system and energy expenditure in amateur esports players to show whether esports can be considered as physical strain or mental stress or whether amateur esports has to be seen as purely sedentary behavior. Methods: Thirty male subjects participated in a 30-minute gaming session, playing the soccer simulation game FIFA 20 or the tactical, first-person multiplayer shooter Counter-Strike: Global Offensive. Respiratory and cardiovascular parameters, as well as energy expenditure, blood glucose, lactate, and cortisol, were determined pre-, during, and post-gaming. Results: There were no significant changes in oxygen uptake, carbon dioxide output, energy expenditure, stroke volume, or lactate levels. Heart rate, blood glucose and cortisol decreased through the intervention until reaching their minimum levels 10 min post-gaming (Cortisolpre: 3.1 ± 2.9 ng/ml, Cortisolpost: 2.2 ± 2.3 ng/ml, p < 0.01; HRmin0.5: 82 ± 11 bpm, HRpost: 74 ± 13 bpm, p < 0.01). Conclusion: A 30-minute esports intervention does not positively affect energy expenditure or metabolism in amateur esports players. Therefore, it cannot provide the same health-promoting effects as traditional sports participation, but could in the long-term rather cause the same potentially health-damaging effects as purely sedentary behavior. However, it does not trigger a negative stress response in the players. Deliberate physical activity and exercise routines adapted to these demands should therefore be part of the daily life of amateur esports players.